Intra-Organisational Trust and Home Care Services: A Study of the Process of Implementing Trust Based Practices in Municipal Eldercare in Sweden - Elmersjö, Magdalena; Sundin, Elisabeth (Scandinavian Journal of Public Administration, 2021)
This article contributes to the discussion concerning intra-organisational trust in home care services. The article is based on a study of organisational change and the implementation process for trust-based management in a Swedish municipality. Collection of material involved several organisational levels in the municipality’s home care service and consists of individual interviews, group interviews, observations and a document review. The results show that the municipality has addressed common problems in home care services in Sweden, resolving them with specific solutions that are unique to the municipality. Quality assurance is performed by allowing frontline employees to fully utilise their competences. Management, first line management in particular, is characterised by checks instead of controls. This is in line with the idea of intra-organisational trust and is achieved by building trust between employees with different levels of education and occupations in the organisation. This form of intra- organisational trust is labelled inter-occupational trust. The process of implementing trust-based practices in the municipality is characterised by three quality dimensions: continuity, flexibility and time allocation. These dimensions are central aspects of the arguments for a user’s perspective on collaboration. An important prerequisite in the municipality studied was that organisational change was followed up with adequate resources in the form of working hours, working conditions, education and training.